Indian Buddhist studies on non-Buddhist theories of a self : the studies of Śāntarakṣita and Kamalaśīla on the Nyāya-Vaiśeṣika, Mimāṃsā, Sāṃkhya, Jain, Vedānta and Vātsiputriya theories of a self /: the studies of Śāntarakṣita and Kamalaśīla on the Nyāya-Vaiśeṣika, Mimāṃsā, Sāṃkhya, Jain, Vedānta and Vātsiputriya theories of a self. (2022) - Duerlinger, James
No abstract available